William Faulkner (1897-2003) some reflections on Absalom, Absalom! - Alfredo Sandoval Gomez (Universidad del Magdalena, 2014)
The moral malaise that afflicts the inhabitants of the American South in the twentieth century and the origin of that trauma for the crime of slavery are addressed in Absalom, Absalom! (1,936). Through Thomas Sutpen, the tragic hero of the piece, and its history, the existing truth is questioned after the Confederate myth, so we can judge the moral responsibility of the pioneer Quine believes in a dismal replica Mississippi Southern society that preceded the Civil War, he being also the destroyer. The four generations of Sutpen spread like a plague damn parental crime, and feeling guilty spectra become of this. The work of certain features of American individualism are deducted, for example the need to be recognized as persons. As the biblical King David, and of which Faulkner derived the title of his work, Thomas Sutpen emerges from its own power over their fellow men, violates the moral code and produces suffering in their children. Both in the house of David and the retribution Sutpen takes the form of violent crime, rebellion, incest, fratricide, the parallels in history are not extensive but significant enough to indicate the human condition century after century .